Profil penurunan tekanan darah pasca induksi dengan anastesi umum di RSUP Sanglah periode Juli-Desember 2016 - Gusti Ayu Amalindasari Prabayastita Masta; I Wayan Suranadi; Dewa Ayu Mas Shintya Dewi (E-Jurnal Medika Udayana, 2018)
Induction of intravenous anesthesia is the process of lulling the patient through anesthetic drugs until the patient enters the anesthesia stage. One of the common anesthesia drugs used in the induction of anesthesia is propofol and the induction of fentanyl. The use of propofol at induced doses causes a significant change in hemodynamic stability in the form of decrease in hemodynamic. Decrease in that parameter can lead to tissue hypoxia, myocardial ischemia, shock to death. The design of cross-sectional descriptive research obtained through secondary data is medical records in the period from June 2016 to December 2016 Sanglah Hospital in patients with elective surgical upper arm fractures with general anesthesia induction. The subjects were 39 patients who met the inclusion and exclusion criteria and received treatment with general anesthesia. Then, recording parameters of hemodynamic changes in systolic blood pressure, diastolic blood pressure, mean arterial pressure (MAP) were assessed at the time of induction of anesthesia. In patients with upper arm bone surgery most were men in 39 cases in the 20-40 year age range with ASA I and received general anesthetic induction of propofol and fentanyl. Post induction in the hemodynamic parameters decreased at systolic blood pressure of 10.42%, then diastolic blood pressure decreased by 2.5%, mean arterial pressure (MAP) decreased by 5.9%. There is a decrease of hemodynamic parameters of both systolic, diastolic and MAP blood pressure in post-induced patients with propofol and fentanyl induction. Keywords: propofol, fentanyl, hypotension